CO Gas Detection of Al-Doped ZnO Nanostructures with Various Shapes - Wang, Byung-Yong; Lim, Dae-Soon; Oh, Young-Jei (IOP PUBLISHING LTD, 2013)
Nanostructure of semiconductor type gas sensors that are high sensitivity, fast response time, inexpensive, and easily fabricated, is suggested. One-dimensional (1D) nanostructures, such as nanorods, and hollow spheres, are attracting particularly great interest because of their large specific surface area and their inherent physical properties. This study combined with ZnCl2 (6.95 g, Sigma-Aldrich), Al(NO3)(3)center dot 9H(2)O (Junsei), NaOH, ethanol, and deionized water (DI) by hydrothermal synthesis to manufacture, spherical, hollow, hierarchical, and nanorod. The same Al-doped ZnO (AZO) were prepared by a colloidal template on a Si wafer to make a 3D igloo structure as well. Sensitivity to carbon monoxide at 50 ppm was tested at 250 degrees C the compare the sensing properties. Gas sensitivity of the hierarchical structure showed the highest sensitivity at 31.8, a figure 7 times that of the packed spherical sphere, whereas the igloo structure gave the fastest response speed of 32 s. The results of various shapes of the AZO nanostructures demonstrated high sensitivity and quick response time, which is useful in the detection of harmful gases in automobiles and the atmosphere. (C) 2013 The Japan Society of Applied Physics
Keywords: SENSOR; FILM; TEMPERATURE; METAL; TIO2